2017
DOI: 10.18203/2349-3291.ijcp20171702
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of premature babies with RDS using bubble CPAP

Abstract: Background: Respiratory distress syndrome (RDS) contributes significantly to mortality and morbidity. Continuous positive airway pressure (CPAP), when applied to premature infants with RDS, re-expands collapsed alveoli, splints the airway, reduces work of breathing and improves the respiration. Objectives: To ascertain the immediate outcome of preterm infants with RDS on Bubble CPAP and identify risk factors associated with its failure.Methods: This was a prospective analytical study and inborn preterm infants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
4
2
1
Order By: Relevance
“…The greater proportion of gestational age made this variable an insignificant predictor. This finding was different from that in the study by Koti et al, 3 Pillai et al, 9 and Arora et al, 7 which claimed no antenatal steroid was proven to be a predictor of nasal CPAP failure. Based on standard operating procedures in the Department of Obstetrics and Gynecology of Dr. Sardjito Hospital, women with gestational age 24+ 0 to 33+ 6 weeks with PROM received antenatal steroids.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…The greater proportion of gestational age made this variable an insignificant predictor. This finding was different from that in the study by Koti et al, 3 Pillai et al, 9 and Arora et al, 7 which claimed no antenatal steroid was proven to be a predictor of nasal CPAP failure. Based on standard operating procedures in the Department of Obstetrics and Gynecology of Dr. Sardjito Hospital, women with gestational age 24+ 0 to 33+ 6 weeks with PROM received antenatal steroids.…”
Section: Discussioncontrasting
confidence: 88%
“…It was probably due to the small number of our sample and the variability of subjects. 40% of our subjects had average gestational age of ≥32, while the reports by Dargaville et al, 5 Bhat et al, 6 and Arora et al, 7 showed the average gestational age of 32 weeks. The majority of our subjects (92.5%) with singleton had a risk of nasal CPAP failure 4.47 times than twins.…”
Section: Discussionmentioning
confidence: 46%
“…28 In our study, there was a significant association between the use of antenatal steroids and the success of early CPAP. These data agree with those reported by Tavares et al 29 and Arora et al 30 Similarly, there was a strong association between PROM and the need for early CPAP, which was consistent with the observations of Pillai and coworkers. 28 We did not find any relationship between Apgar scores at 1 minute and the use of early CPAP.…”
Section: Discussionsupporting
confidence: 93%
“…Complications were not seen in 69.3% of our patients which is similar to the observation made by Ahmed et al where 75% of their patients had no complications relating to NBCPAP. 16 In this study, low gestational age was one of the predictors for failure of NBCPAP which was in agreement with studies by Adb-Allah et al, Arora V et al and Pillai MS et al [16][17][18] Prematurity is related to apnea and cardiovascular instability which results in increased severity of disease necessitating mechanical ventilator and thus failure of NBCPAP. Ten newborns needed to be shifted to mechanical ventilation due to worsening condition.…”
Section: Discussionsupporting
confidence: 90%